LITERASI DIGITAL SEBAGAI LANGKAH AWAL SISWA DALAM MEMBERANTAS HOAX DAN UJARAN KEBENCIAN - Permana, Sulwan; Ramadhan, M. Zilhan Salman; Fatah, Muhamad Abdu; Anwar, Saepul; Rohmah, Siti; Ibrahim, Galih; Farhani, Siti Aulia; Sastradipraja, R Muhammad Arya Fajar; Rizky, Muhammad Naufal; Arif, Zaenal; Nurlatifah, Sarah; Rohman, Asep Abdul; Al-Husein, Fajar; Ramdhani, Tio; Muharam, Muhammad Faisal; Jamami, Yadziz Siddik Al; Kristiawan, Diky; Muhammad, Faiz Mahatir; Ananta, Asti; Putri, Icha Aulia; Saumi, Ira Nurachma; Imamudin, Imamudin (Institut Teknologi Garut, 2024)
Digital literacy is a competency that includes the ability to understand, use and assess information available through various digital platforms. These skills include not only the technical use of technology, but also the ability to assess the credibility of information and apply ethics in a digital environment. In the ever-growing information era, digital literacy is becoming increasingly important for active participation in digital society, both in the context of education, work and everyday life. The main challenges in increasing digital literacy include gaps in access to technology, lack of adequate education, and the risk of spreading misinformation. Students who are still vulnerable to hoaxes and hate speech need to be given understanding through digital literacy. The aim of this digital literacy activity is to provide students with an understanding of hoaxes and hate speech. Therefore, digital literacy must be seen as an essential competency that is not only technical, but also includes social aspects that are crucial in facing the dynamics of today's digital world.